Faktor-faktor kejayaan perlaksanaan sistem kualiti ISO9000 di dalam industri pembinaan di Malaysia - Mohamad @ Ahmad, Khairil Azizi (2006)
In order to get a better quality result, the implementation of a precise quality system is necessary in any organization. ISO9000 system was developed in 1987 to suit this objective. In Malaysia, this system grow rapidly with a lot of company in every industry including construction tries to get its recognition. This study is conducted to determine the factors for construction companies to successfully implement ISO9000 system. The methodology adopted is through literature review, interview and questionnaire to respondents who are directly or indirectly involve with ISO9000 system in construction industry. The procedures in implementing ISO9000 are reviewed and the data collected through interview and questionnaire are analyzed using statistical and frequency analysis. The findings are six benefits of ISO9000 implementation such as by implementing ISO9000 system its helps in company promotion, the company getting more recognition and getting better business opportunities. Among the problem in implementation of the ISO9000 system are additional works procedures, heavy load documentation and extra working hours. Among the ten critical factors for success in ISO9000 implementation are top management involvement, reward for good quality produces, an internal audit for the purpose of ISO9000 implementation, management monitoring, education and trainings for the workers in ISO9000 implementation. The other factors related to the success in implementing ISO9000 found in this study also must not be ignored since its play important roles in the success of implementation of ISO9000 system for several companies. The findings of this study hopefully will serve as an important guide to the construction related companies for better ISO9000 system implementation.